DESKRIPSI VARIAN PERMAINAN TRADISIONAL DAERAH NUSA TENGGARA BARAT - Ashar Pajarungi Anar; Nurul Kemala Dewi; Mohammad Archi Maulyda; Nursaptini Nursaptini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
We can find various types of electronic devices that are so sophisticated followed by the emergence of various types of modern games or online games that can be so easily accessed by children. So that at this time traditional games are becoming obsolete and modern or online games are preferred. The type of research used is descriptive qualitative research and data collection techniques carried out by observation, interviews and documentation. The traditional games originating from the province of West Nusa Tenggara, namely, the first traditional games originating from Lombok such as Lunglungse Games, Manuk Kurung Games, Jumpring Games, Shopping Games, and Game Peresean. The Sumbawa Traditional Games are Logok Game, Rabanga Game, Kebo Play Game, and Karaci Game. The Bima Dompu Traditional Games are Mpaa Sila Games, Baleba Games, and Parise Games. The benefits of knowing the types of traditional games so that Indonesian people especially the people of West Nusa Tenggara province can add more insight and are expected to be preserved so that they are not extinct.